Chemical safety in school laboratories located in urban and rural areas: a case study in Cameron Highlands, Malaysia - Nur Liyana Ali,; Goh, Choo Ta; Sharifah Zarina Syed Zakaria,; Mazlin Mokhtar,; Sharina Abdul Halim, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2018)
School laboratory is one of the important facilities in enhancing teaching and learning particularly for science related subjects. Once students learned about science theories in the classroom, they can apply what they have learned by setting up relevant experiment in the school laboratories. However, potential risks occur in the laboratories, especially when dealing with chemicals. As this is unavoidable, hence, safety measures such as good ventilation system, personal protective equipment, emergency response plans are in place to safeguard the users and the environment. Nonetheless, existing safety measures in schools might vary among each other. A project was embarked to investigate if there have differences between secondary schools located in urban and rural areas, particularly on existing safety measures in laboratories, practices and awareness of students. This paper presents the preliminary findings of three aspects in chemical safety: level of knowledge, level of practices and level of perspective among the students in urban and rural areas in Pahang. The findings indicated that there were no differences between the levels of students’ knowledge, practices and perspective of chemical safety in school laboratories. Majority of the students had average level of knowledge and practices of chemical safety. The study also revealed that they not so sure about the safety aspects in school laboratory. The findings from this study provide basic information for teaching and learning to enhance the knowledge and practice of chemical safety in school laboratories by taking considerations from students’ perspective.